(untitled) (Scripta : English Department Journal, 2026)
The rapid development of artificial intelligence (AI) technology has significantly transformed English language learning in higher education. In many English Foreign Language (EFL) learning contexts, students frequently experience difficulties related to grammar understanding, vocabulary mastery, writing development, speaking confidence, and independent English practice. The emergence of ChatGPT as an AI-assisted learning tool has provided new opportunities for students to access flexible, interactive, and personalized learning support anytime and anywhere. Therefore, this study aimed to investigate students’ and lecturers’ perceptions regarding the integration of ChatGPT in English language learning at STIE Rajawali Purworejo. This study employed a qualitative descriptive research design involving twenty students and one English lecturer. The research was conducted from November to December 2025. Data were collected through questionnaires and in-depth interviews and analyzed using thematic analysis. The findings revealed substantial differences in students’ learning experiences before and after the implementation of ChatGPT. Before using ChatGPT, students experienced difficulties in generating ideas, understanding grammar, developing vocabulary, and practicing English independently. However, after the integration of ChatGPT, students perceived English learning as more interactive, flexible, motivating, and accessible. The findings also indicated that ChatGPT positively influenced students’ motivation, engagement, confidence, writing development, and autonomous learning. Furthermore, the lecturer perceived ChatGPT as an effective educational tool that supports students’ participation, language development, and independent learning. Nevertheless, concerns regarding students’ overdependence on AI-generated responses, reduced critical thinking skills, and academic integrity were also identified. Therefore, the study concludes that ChatGPT has considerable potential to enhance English language learning when implemented responsibly through proper pedagogical supervision and ethical guidance.